Thy-1 Deficiency Augments Bone Loss in Obesity by Affecting Bone Formation and Resorption - Picke, Ann-Kristin; Campbell, Graeme M.; Schmidt, Felix N.; Busse, Björn; Rauner, Martina; Simon, Jan C.; Anderegg, Ulf; Hofbauer, Lorenz C.; Saalbach, Anja (Frontiers in Cell and Developmental Biology, 2018)
Accumulation of adipose tissue in obesity was reported to be both protective and deleterious to bone health. Recently, Thy-1 was discovered to stimulate osteogenic differentiation of mesenchymal stem cells while it concurrently reduces adipogenic differentiation. Therefore, Thy-1 positively regulates bone mass and strength. We aimed to obtain mechanistic insights into how increased fat accumulation negatively affects bone mass and bone formation. Therefore, we investigated the impact of Thy-1 on bone metabolism under 12-weeks high fat diet (HFD)-induced obese conditions by µCT, histological analysis and Fourier-transform infrared spectroscopy (FTIR). Indeed, mice lacking Thy-1 showed increased body fat mass after HFD compared to WT mice. In parallel, obese Thy-1-deficient mice displayed a reduced trabecular bone volume (-38%) and bone formation (-57%). FTIR analysis showed that the mineral-to-matrix ratio decreased (-8%) and the carbonate-to-phosphate ratio increased (+5%) indicating changes in collagen amount and mineral age, respectively. In contrast to lean mice, under obese conditions, lack of Thy-1 affected both osteoblast and osteoclast function. Elevated numbers of osteoclasts (+39%), increased expression of tartrate-resistance acid phosphatase (+86%), and higher serum levels of collagen type 1 cross-linked N-telopeptide (+30%) in obese Thy-1-deficient mice indicated that Thy-1 promotes osteoclast activity under obese conditions. Analysis of bone marrow fat revealed a dramatic increase (+56%) associated with strongly upregulated tumor necrosis factor α expression (+46%) in Thy-1-deficient compared to obese WT mice. In summary, our findings show that in obesity lack of Thy-1 results in a reduced bone mass due to an increased adipogenic and decreased osteogenic differentiation as well as by concurrently increased osteoclast differentiation. Increased TNFα expression caused by an amplified fat tissue accumulation might be responsible for elevated osteoclast activity in obese Thy-1-deficient mice.